Análisis financiero de la Cooperativa de Transportes Loja, periodo 2012-2013 - Merino Puchaicela, Fabiola Katherine (2016)
The research work entitled "FINANCIAL ANALYSIS OF COOPERATIVE TRANSPORT LOJA, PERIOD 2012-2013", was conducted in order to determine the financial position of the company, through the application of techniques and procedures of financial analysis, as the Vertical Analysis, Horizontal and use of financial indicators, helping to improve efficiency and therefore the growth of it. For its development was raised as General Objective: Apply the Cooperative Financial Analysis Transport Loja, periods 2012-2013 to meet its economic and financial situation and guide better decision-making; for which the following objectives were determined: The first objective is: "To develop the vertical and horizontal analysis, which will determine the structure and changes in the various accounts of balance" with the application of vertical analysis financial structure arriving to determine met by 2013 that total assets having a value of $ 6,474,267.29 representing 100% the same as they are funded by liabilities as a percentage of 31.87% and 68.13% corresponds to equity, which means that most of the assets belonging to members of the Cooperative. Likewise, the horizontal analysis, where variations presented each of the accounts included in the balance sheet developed evidenced both financial and economic situation has had during the periods under study, where assets increased the amount of $ 1,098 535.81 representing 20.44% situation especially given the 6 heritage as it amounted to $ 698,847.97 representing 18.83% and secondly by liabilities with a total value of $ 339,687.84 that is 24 03%. In the Profit and Loss expenses show an increase of 13.23%, while revenue increased 23.46% with a notable increase in the surplus for the year of 2.421.45% in absolute terms are $ 627,622.91. The second objective is to apply Financial Ratios Balance Sheet and Income Statement of the Cooperative, which has been obtained that by the year 2013 the liquidity level is $ $ 1.00 inferring that only has to cancel its obligations; The activity indicators show a permanence of inventory of 22 days, receivables turnover of 42 days and accounts payable 88 days, giving a margin of 24 days to invest the money available since first performed the collection of subsequently cancel their accounts for short-term obligations; Regarding the debt is 31.87%, meaning their debt is moderate as it is not in the hands of others and finally presents a return on assets of 15.57% and on capital of 47% return quite attractive to partners. The third specific objective is: "Making the operational and financial leverage to determine the fixed and variable costs as a basis for the point of balance", ie the Cooperative has 2013 operating leverage of 14, 96% and, financial leverage of 60,09%, where the company must generate an income level of $ 6.031.394,81 with an installed capacity of 75,10% being the point of balance to cover other costs and expenses for later no gain, no loss, no gain. 7 The fourth specific objective is: "To present the report of the Financial Analysis managers Cooperative Transport Loja", which is directed to the manager of the cooperative where the results of the application of financial analysis is detailed in summary states the cooperative financial years 2012 and 2013 and recording the respective conclusions and recommendations in one way or another help managers to solve the deficiencies found in the analysis practiced Cooperative allowed. The methodology is based specifically on the use of scientific, deductive, inductive, analytic, synthetic, mathematical and statistical method that enabled them to perform research work in a systematic and orderly. Finally, the directors of the cooperative to be carried out periodically the vertical and horizontal analysis, so they can know exactly the effectiveness of its operations, both in its growth or decline and the application of financial indicators, especially recommended: liquidity, activity, indebtedness and profitability, for taking the right decisions to boost the economic and financial development of the same.